The burden of moderate-to-heavy soil-transmitted helminth infections among rural malaysian aborigines: an urgent need for an integrated control programme - Ahmed, A.; Al-Mekhlafi, H.M.; Choy, S.H.; Ithoi, I.; Al-Adhroey, A.H.; Abdulsalam, A.M.; Surin, Johari (BMC, 2011)
Background: Soil-transmitted helminth (STH) infections, among the most common neglected tropical diseases, continue to be a major threat to the health and socioeconomic wellbeing of infected people especially children in developing countries. Methods: A cross-sectional study among 254 aboriginal schoolchildren was conducted in order to determine the current prevalence and intensity of infections and to investigate the potential risk factors associated with moderate-to-heavy burden of STH infections among these children. Results: Overall, 93.7 of children were found to be infected with one or more STH species. The prevalence of trichuriasis, ascariasis and hookworm infections were 84.6, 47.6 and 3.9, respectively. Almost half of the participants had heavy trichuriasis, one-quarter had heavy ascariasis whereas all hookworm infections were light infections. Overall, moderate-to-heavy STH infections accounted for 56.7 of the total infections. Univariate analysis revealed that those using untreated water supply (P = 0.013), living in houses without toilets (P = 0.027) and having domestic animals in the houses (P = 0.044) had significantly higher prevalence of moderate-to-heavy infections than others. Logistic regression analysis confirmed using untreated water for drinking (P = 0.001) and the absence of a toilet in the house (P = 0.003) as significant risk factors of moderate-to-heavy STH infections among these children. Conclusion: The high proportion of moderate-to-heavy STH infections further confirms the need for serious attention towards these devastating diseases that has put lives and the future of aboriginal children in jeopardy. Introduction of more poverty alleviation schemes, proper sanitation, provision of clean and safe drinking water, health education, as well as the introduction of periodic school-based deworming programmes are imperative among these communities in order to curtail the transmission and morbidity caused by STH.